Conceptual Study of Trimarma W. S. R. to Sirah Marma - Gaun, Mritunjay; Mishra, Vikas; Kumar, Vinod; Gupta, Shayam Sundar (International Research Journal of Ayurveda & Yoga, 2023)
The science of Marma (vital point), i.e., Marma Vijyaniyam is an extraordinary and dynamic part mentioned in classical texts of Ayurveda that has tremendous value while performing surgery. Marma is such an imperative and unique principle of Ayurveda. Trimarma is the basic organs of the body representing the three different systems – nervous, cardiovascular, and urinary system. Trimarma is gaining importance as “tripod of life” because they are more Sadyopranahara Marma than other Marma. Sirah Marma is considered first because trauma to the head causes disturbance in respiratory, circulatory, and temperature-regulating center in the brain area and may lead to unconsciousness and death. Charak stated that Prana is situated in Siras which is also called Uttamangam due to its control over all the Indriya (Sense). In this article, an effort is made to compile and analyze the fundamental concept of Trimarma. Marmas are certain vital points spread all over the surface of the human body. The Marma is said to be the sites where there is the conglomeration of Mamsa, Sira, Snayu, Asthi, and Sandhi and at these places, Prana resides, especially by nature.[1] Marma is constituted by six vital elements, i.e., Soma, Maruta, Tejas, Satva, Raja, and Tama and where Jivatma resides. Hence, any injury to Marma proves to be fatal.[2] All the classics analogously opine for 107 Marma[3] in the body but on point of narration, only three of them – Trimarma – Sirah, Hridaya, and Vasti are mentioned. Marma of the trunk is more vital than the Marma of extremities, as the extremities are connected to and depend on the trunk. Even among the Marma of trunk, Trimarma is more important.